If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 10v = 0 Reorder the terms: 10v + 5x = 0 Solving 10v + 5x = 0 Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-5x' to each side of the equation. 10v + 5x + -5x = 0 + -5x Combine like terms: 5x + -5x = 0 10v + 0 = 0 + -5x 10v = 0 + -5x Remove the zero: 10v = -5x Divide each side by '10'. v = -0.5x Simplifying v = -0.5x
| 136=4(-7x-8) | | 3(9s+7)-12s=3(5s+1)-5 | | -117=-8(-6-5x)-5 | | 33=5+12+c | | 33=5+12 | | 3(y+6)=4(y-2) | | x^2+0.5x=0.68 | | 6x+11y=57 | | 3x-4=2x-9 | | c=b(x+3) | | cos(7x)=cos(5x)+sin(x) | | 0=3(-3)-1 | | 3x+9=4x-3 | | 3x+9=4x-8 | | 4/2+4/7= | | (5x-4)+(6x-5)= | | 9m+11=4m-4 | | 0.05(5t-1)=0.25(t+1)-0.30 | | y=7^8/8+6 | | 22=4k-6 | | 24t^2+23t-12=0 | | -5x-13=3x+11 | | 4x+18=5(x+2) | | 2(x+5)+7=6x-4(-3+x) | | 3(x+3/7)-7 | | 5x-4=5(x-3) | | 3(x*3/7)-7 | | 4a-3b=a | | 6(4x-1)=24x-6 | | 4+3r-1=9r+17-4r | | -18k+11l+20-8k+32-4l= | | 2p-4p-8p+16= |